A funny thing happened on the way to the future [compact disc, unabridged] : twists and turns and lessons learned - Fox, Michael J., 1961- (Hyperion Audio, 2010)
Drawing on lessons learned before and during his celebrated career as well as his harrowing struggles with Parkinson's disease, famed actor Michael J. Fox presents a poignant memoir about achieving success and capitalizing on personal strengths